2017
DOI: 10.1016/j.aap.2017.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Young females at risk while driving with a small child

Abstract: Introduction: Previous research suggests that young mothers with little driving experience are at risk when driving with a small child passenger. In this study we examined the prevalence, characteristics and risk of fatal motor vehicle crashes involving an infant passenger under the age of one among female drivers of different ages. Methods:We used crash data from the US Fatality Analysis Reporting System for 1994-2013. The prevalence of fatal crashes involving infants was examined by age of female drivers and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 39 publications
1
13
0
Order By: Relevance
“…In short, the network of driving behaviors can be seen as being in two qualitatively different states distinguished by the connection strengths between the behaviors. As another example, it has been shown that young mothers have an elevated crash risk when driving with an infant passenger compared to driving alone (Maasalo, Lehtonen & Summala, 2017); the dynamics of their behavior in these contexts are likely to differ.…”
Section: Discussionmentioning
confidence: 99%
“…In short, the network of driving behaviors can be seen as being in two qualitatively different states distinguished by the connection strengths between the behaviors. As another example, it has been shown that young mothers have an elevated crash risk when driving with an infant passenger compared to driving alone (Maasalo, Lehtonen & Summala, 2017); the dynamics of their behavior in these contexts are likely to differ.…”
Section: Discussionmentioning
confidence: 99%
“…In short, the network of driving behaviors can be seen as being in two qualitatively different states distinguished by the connection strengths between the behaviors. As another example, it has been shown that young mothers have an elevated crash risk when driving with an infant passenger compared to driving alone 58 ; the dynamics of their behavior in these contexts are likely to differ.…”
Section: Discussionmentioning
confidence: 99%
“…Current studies have revealed several findings concerning this area of study. Among social factors that influence driving behaviors, child occupancy is a crucial factor, especially for young females with a child ( 19 ). Children’s behavior can lead to driver distraction and sometimes can increase the potential of crashes ( 20 , 21 ).…”
Section: Literature Reviewmentioning
confidence: 99%